Increasing the Student’s Vocabulary Mastery by Using List Group Label Strategy - Yosef Yanuarius Zega; Kristof Martin Efori Telaumbanua; Hidayati Daeli; Yaredi Waruwu (Edumaspul: Jurnal Pendidikan, 2023)
Vocabulary is an important component in learning English that should be mastered by students before mastering the four skills in English. However, the students had several problems in vocabulary mastery that caused the students were not able to comprehend the written descriptive text so that the students were not able to achieve the MCC. Therefore, the purpose of research was to increase the students’ vocabulary mastery by using List Group Label Strategy. The researcher used the Classroom Action Research method as research design that was held on in two cycles. The results of the research showed that in Cycle I most of students were not able to achieve the MCC, there were 4 students (15%) in “Very Good” level, 11 students (42%) in “Good” level, 9 students (35%) in “Enough” level, 2 students (8%) in “Less” level. The average of students score in Cycle I was 69.61. While the result in Cycle II showed that all of students have passed the MCC, there were 11 students (42%) in “Very Good” level, and 15 students (58%) in “Good” level. The average of students score in Cycle II was 85.57. Based on the results of the research, it proved that List Group Label Strategy increases the students’ vocabulary mastery.